Photosynthetic responses and protective mechanisms under prolonged drought stress in cocoa - Suárez-Salazar, Juan Carlos; Guaca-Cruz, Lised; Quiceno-Mayo, Esther Joaquina; Ortiz-Morea, Fausto Andrés (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the impact of a prolonged period of moderate and severe drought on the growth and photosynthetic capacity of seminal cocoa seedlings of the IMC-67 genotype under tropical nursery conditions. Under conditions of humidity of 84–90%, temperature of 25–28°C, and radiation of 600–900 µmol m-2 s-1, the seedlings were subjected to the following treatments: moderate (-1.68±0.05 MPa) and severe (-2.68±0.05 MPa) water stress; and a control, without stress (-0.92±0.02 MPa). Photosynthetic light response curves, chlorophyll a and b fluorescence parameters, and content of proline and photosynthetic pigments were evaluated. Cocoa seedlings subjected to prolonged drought stress show a reduced photosynthetic capacity and growth, which highlights their sensitivity to water scarcity. Adaptive growth responses are evident as seedlings adjust their height and leaf production to available water, showing their resilience to environmental stress. The seedlings activate protective mechanisms, such as increased non-photochemical quenching and elevated carotenoid and proline levels, which help mitigate the effects of a decreased stomatal conductance and photosynthetic pigment content under drought conditions.